1957
DOI: 10.1002/hlca.19570400533
|View full text |Cite
|
Sign up to set email alerts
|

Aminoacyl‐Einlagerung. 1. Mitteilung. Definition, Übersicht und Beziehung zur Peptidsynthese

Abstract: zum 60. Geburtstag gewidrnet. (29.y. 57.) 1. Mitteilung. ~ ~~ , ) J . P. Zimmermann, Dissertation Universitat Basel, 1952. za) J . P. Zirnmermann, unveroffentlicht. 3, J . WehrmiiZZer, Dissertation Universitat Basel, 1955. 4, P. Quitt, Dissertation Universitat Basel, 1956. , ) Ob auch im Fall der Imidazolonbildung von AAE zu sprechen sei. ist rine Ermessensfrage. Wir werden bei spaterer Gelegenheit dirauf znriickkommen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

1986
1986
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(14 citation statements)
references
References 26 publications
1
13
0
Order By: Relevance
“…The foundation for such a type of technique was laid by Brenner et al more than 60 years ago. 130 Recently, Miranda et al reported the use of a 2-hydroxy-6-nitrobenzyl auxiliary with the intention of improving the efficiency and yield of peptide synthesis including the couplings involving sterically hindered amino acids. 131 Initially, through reductive alkylation, the auxiliary is attached to a resin-bound peptide.…”
Section: O-acyl Isopeptide Methods (Click or Switch Peptides)mentioning
confidence: 99%
“…The foundation for such a type of technique was laid by Brenner et al more than 60 years ago. 130 Recently, Miranda et al reported the use of a 2-hydroxy-6-nitrobenzyl auxiliary with the intention of improving the efficiency and yield of peptide synthesis including the couplings involving sterically hindered amino acids. 131 Initially, through reductive alkylation, the auxiliary is attached to a resin-bound peptide.…”
Section: O-acyl Isopeptide Methods (Click or Switch Peptides)mentioning
confidence: 99%
“…The described strategy holds the flexibility in synthesizing both N‐ and O‐linked glycopeptides/glycoproteins by suitably selecting the sugar substrate with appropriate functionality at the anomeric position and coupling it to side chain functionalities like hydroxyl (Thr, Ser) or carboxylates (Asn)17, 18. The flexibility of the ligation site revealed the importance of proximity effect as well as the significance of having primary amine in a similar fashion as revealed by studies on amine capture strategy for peptide bond formation through ON acyl transfer performed by Brenner et al ,22 Wieland et al ,23 and Kemp24. One important difference in NCL and SAL is the rate limiting step.…”
Section: Introductionmentioning
confidence: 94%
“…At the very beginning of chemical peptide synthesis Theodor Wieland [104] and Max Brenner [166] independently had the idea to convert the bimolecular reaction between two peptides to be ligated into an intramolecular reaction by bringing together the respective C-and N-termini on a template in order to facilitate intramolecular acyl transfer reaction. A similar mechanism is realized practically in the reverse ligase action of serine and cysteine proteases in which O-or S-acyl intermediates undergo an O-or S-to N-acyl transfer reaction forming a peptide bond.…”
Section: Prior Capture-mediated Ligationmentioning
confidence: 99%
“…The principle of a template-mediated amide bond formation according to Brenner et al [166] using a salicylamide template ( Figure 5.20) is based on a base-catalyzed intramolecular rearrangement [168]. Demonstrated in a general sense, the carboxy function of salicylic acid is acylated with an amino acid alkyl ester, whereas the hydroxy group is esterified with a protected amino acid.…”
Section: Template-mediated Ligationmentioning
confidence: 99%